TEORI SIBERNETIK DAN IMPLIKASINYA TERHADAP MODEL PEMBELAJARAN BRAIN BASED LEARNING PADA PEMBELAJARAN PKN - Damayanti, Siska; Suryadi, Karim (Prodi PPKn Universitas Slamet Riyadi, 2023)
The world of education, especially Civics learning, requires innovation and variation in the learning methods applied. The brain-based learning method is very interesting because optimizing brain work can be started in a simple way. Educators' knowledge of fundamental questions about